2021
DOI: 10.3389/fendo.2021.618213
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes and Autoimmune Thyroid Disease—The Genetic Link

Abstract: Type 1 diabetes (T1D) and autoimmune thyroid disease (AITD) are the most frequent chronic autoimmune diseases worldwide. Several autoimmune endocrine and non-endocrine disorders tend to occur together. T1D and AITD often cluster in individuals and families, seen in the formation of autoimmune polyendocrinopathy (AP). The close relationship between these two diseases is largely explained by sharing a common genetic background. The HLA antigens DQ2 (DQA1*0501-DQB1*0201) and DQ8 (DQA1*0301-DQB1*0302), tightly lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 143 publications
2
58
1
1
Order By: Relevance
“…Although IFIH1, RSAD2, and PARP9 were found to be associated with a variety of autoimmune or inflammatory disease development, such as SLE, RA, Sjögren’s syndrome (SS), type 1 diabetes (T1D), and AITD ( Frommer and Kahaly, 2021 ; Zedan et al, 2021 ), we did not find that these genes were differentially expressed between the recurrent GD group and the normal group. Ubiquitin-specific peptidase 18 (USP18) plays a crucial role in the development of Th17 cells and can regulate the differentiation and function of Treg cells ( Yang et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 69%
“…Although IFIH1, RSAD2, and PARP9 were found to be associated with a variety of autoimmune or inflammatory disease development, such as SLE, RA, Sjögren’s syndrome (SS), type 1 diabetes (T1D), and AITD ( Frommer and Kahaly, 2021 ; Zedan et al, 2021 ), we did not find that these genes were differentially expressed between the recurrent GD group and the normal group. Ubiquitin-specific peptidase 18 (USP18) plays a crucial role in the development of Th17 cells and can regulate the differentiation and function of Treg cells ( Yang et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 69%
“…The results suggested a significant association between miRNA-499 rs3746444 polymorphisms and RA risk [ 17 ]. Each autoimmune disease has its characteristics, but recent researches found that some autoimmune diseases share several common mechanisms [ 53 55 ], and genetic studies have shown that different autoimmune diseases can largely share the same genetic background [ 56 58 ]. People with an autoimmune disease are at risk for another autoimmune disease [ 58 ], and their family members are at increased risk for more than just this autoimmune disease [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-2 receptor alpha (IL2RA) is one of three subunits that make up the high affinity interleukin 2 receptor (IL-2R) [16]. The IL2RA gene, which is found on chromosome 10p15, encodes CD25 and influences the generation and function of regulatory T cells by acting as a differentiation factor and inhibiting autoreactive T cells in the periphery via CD25 [17]. Beata et al [18] found the rs7093069-IL2RA genotype may increase the risk of autoimmune thyroid diseases.…”
Section: Discussionmentioning
confidence: 99%